Android-Based Measurement Design of Leg Muscle Power - Muhammad Irsyad; - Yohandri; - Asrizal; Nurul Ihsan (PILLAR OF PHYSICS, 2022)
Leg muscle power is a combination of strength and speed, or maximal muscle performance at maximum speed. At this time the measurement of leg muscle power is still using manual tools that require a lot of people, and the measurement of leg muscle power is still lacking the jump distance. Based on the problems obtained, the author makes a production Android-based measurement design of leg muscle power. This study aims to determine the performance and specifications of Android-based measurement design of leg muscle power. This research is an engineering study to determine the performance specifications and design of an android-based leg muscle strength measurement tool. Based on the results of the analysis of the data obtained, the performance and design specifications of the tool are obtained. The performance specifications of the tool acquire the mechanical shape of the tool. The tool will automatically measure the strength of the leg muscles, and the measurement results can be viewed via Android. The design specifications are obtained from the characteristics of the sensor, accuracy and precision of the tool. Sensor characteristics can be seen from the load cell and ultrasonic sensors. The accuracy level of the leg muscle explosive power measurement tool obtained is 98.06%, and the instrument precision level obtained is 95.30%.